2013
DOI: 10.1177/0952076713506450
|View full text |Cite
|
Sign up to set email alerts
|

‘Cabined, cribbed, confined, bound in’ or ‘we are not a government poodle’: Structure and agency in museums and galleries

Abstract: This paper is based upon research that has been part-funded by travel grants from the British Academy (SG111848) and De Montfort University to whom many thanks are extended. The same goes to all of the staff in museums and galleries who have allowed me to talk to and question them.2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 65 publications
(92 reference statements)
0
10
0
Order By: Relevance
“…Sharon MacDonald's (2002) Behind the Scenes at the Science Museum is an important theoretical and methodological move in this direction, using ethnography and organizational analysis to understand the complex processes of exhibition making. Another area of work which turns its attention to the organizational features of museums is cultural policy studies which considers how staff implement (or otherwise) policy directives within their situated organizational contexts (Tlili 2008(Tlili , 2012Gray 2014;McCall and Gray 2014). Such work highlights the particular dynamics though which practice is framed, performed and constrained.…”
Section: Community Engagement In Museumsmentioning
confidence: 99%
“…Sharon MacDonald's (2002) Behind the Scenes at the Science Museum is an important theoretical and methodological move in this direction, using ethnography and organizational analysis to understand the complex processes of exhibition making. Another area of work which turns its attention to the organizational features of museums is cultural policy studies which considers how staff implement (or otherwise) policy directives within their situated organizational contexts (Tlili 2008(Tlili , 2012Gray 2014;McCall and Gray 2014). Such work highlights the particular dynamics though which practice is framed, performed and constrained.…”
Section: Community Engagement In Museumsmentioning
confidence: 99%
“…However, taking a organizational view through 'close-up' methodologies opens up opportunities to examine the ability of museum professionals working within institutional arrangements to accommodate, re-write or resist the broader political projects in which museums are enrolled. Significant work here has already been undertaken to understand policy attachment in museums in the ways in which UK museum professionals have revised state directives of 'social inclusion' (Newman and McLean 2004;West and Smith 2005;Tlili 2008;Gray 2014). As museums continue to advocate their social agency, and in the cases where this is expected of museums, then the commitments (or otherwise) of museum professionals to the institutions in which they work becomes a matter of concern.…”
Section: Museums As Peopled Organizationsmentioning
confidence: 99%
“…In the case of attachment in the arts this gap is exploited by those within the arts sector to allow them to seek their own ends even if other policy actors have alternative ends to pursue. More recent work on the museums sector (Nisbett, 2013: Gray, 20142015a;2016) has shown that the control of implementation allows the policy intentions of outside actors to be manipulated in such a way that it appears that instrumentalisation has taken place even though it has not. Policy actors in these cases have adopted the language of policy intentions that derives from other sectors but this is not what drives the specific policy choices that they then make.…”
Section: Local Government and The Arts: Policy Developmentsmentioning
confidence: 99%
“…Extending this argument to other, equally minority, policy sectors and sub-sectors would serve to demonstrate whether the arts are simply sui generis in pursuing attachment strategies or whether it is a more common device that is also utilised elsewhere. The evidence from the museums sub-sector and cultural policy in general clearly indicates that attachment is also pursued there (Belfiore, 2012;Gray, 2008;2014;2015a;2016) but further analysis of other policy arenas is required if the attachment idea is to be successfully extended further. It is possible, for example, to apply the attachment approach to minority policy interests within central policy sectors, such as education, to see both whether it can serve to make sense of how these minority examples operate, and whether it can be generalised as a strategy across policy sectors.…”
Section: Extending the Argumentmentioning
confidence: 99%